Analisis Kemampuan Literasi Numerasi Siswa Ditinjau dari Kecemasan Matematika - Lusiana, Lusiana; Sukayasa, Sukayasa; Pathuddin, Pathuddin; Mubarik, Mubarik (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to describe the literacy and numeracy abilities of class VIII students at SMPN 02 Darmpelas in terms of low, medium and high mathematics anxiety. The method used is a qualitative descriptive method with instruments in the form of mathematics anxiety questionnaires, tests and interviews. The results showed that subjects who had low math anxiety were able to meet 3 numeracy literacy indicators, subjects who had moderate math anxiety were able to meet 2 of the 3 numeracy literacy indicators, and subjects who had high math anxiety were only able to meet 1 of the 3 numeracy literacy indicators. In conclusion, for the category of students with moderate mathematics anxiety, attention needs to be paid to writing down known and asked data in detail and clearly, while for students with high mathematics anxiety, students need intensive guidance from the teacher to understand the methods used in planning problem solving and also in drawing conclusions to obtain correct and appropriate answers. Keywords: Analysis, Math Anxiety, Numeracy Literacy